Rubus macvaughianus sp. no. (Rosaceae), a wild raspberry of possible horticultural interest - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 1989)
Rubus macvaughianus sp. n., a raspberry of excellent flavor, native of Cerro Zamorano in the Guanajuato-Querétaro border area, is described.